Phoneme Form Transformation In The Affixation Process Of Tialo Language: A Morphophonemic Study - Dian Magfira; Rizky Anugrah Putra (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2026)
This study examines morphophonemic transformations during the affixation process in Tialo, a regional language spoken in Tomini District, Parigi Moutong Regency, Central Sulawesi. Utilizing a qualitative descriptive approach with a distributional analysis method, data were collected from five native speakers through observation, elicitation, interviews, and audio recordings. The analysis identifies four types of phoneme transformations: (1) phoneme reduction (62 instances), primarily triggered by confixes such as po-...-ane and po-...-one; (2) phoneme substitution (18 instances), predominantly associated with the suffix -a; (3) phoneme addition (9 instances), triggered by the prefixes mo- and moM-; and (4) phoneme position shifts (6 instances), consistently resulting from the infix -in-. Ultimately, these findings highlight phoneme reduction as the most dominant morphophonemic characteristic in Tialo affixation.